Degradation and Toxicity of Amoxicillin After Electron Beam Irradiation - Sueli Ivone Borrely; Marcelo Miyada Redígolo; Bruno David Quiroz Villardi; Daniel Temponi Lebre; Flavio Kiyoshi Tominaga (Brazilian Journal of Radiation Sciences)
A recent and growing concern in environmental studies is the presence of antibiotics in wastewater, which contributes to antimicrobial resistance building. Amoxicillin, according to the World Health Organization, is one of the most consumed antibiotics worldwide, for being a first line therapy for common infections. Among several drug degradation methodologies, electron beam irradiation (EBI) is presented as an efficient and green treatment. This work presents data on amoxicillin degradation via EBI. Ecotoxicity essays were performed employing Vibrio fischeri, carbon removal efficiency was evaluated by TOC and degradation rate by LC/MS-MS. Chromatographic results indicate a 97.9% drug concentration reduction after 0.75 kGy; TOC results indicate 10% carbon removal at 3.0 kGy; toxicity assays indicate 80% in removal of toxicity at 0.75 kGy and a decrease in efficiency with higher doses. In conclusion, results indicate the 0.75 kGy as most effective for drug removal employing EBI.